Evidence for multi-rifting in the Variscan–Alpine cycle transition: insights from the European western Southern Alps - E. Scaramuzzo; F. A. Livio; M. G. Fellin; C. Maden (Solid Earth)
We investigate the transition between the Paleozoic Variscan cycle and the Mesozoic–Cenozoic Alpine supercontinent cycle, both of which have played a pivotal role in shaping the central European–Mediterranean plate architecture. Two main scenarios have been proposed so far for this transition: (i) a single, long-lasting, Permo-Triassic rifting event, culminating in the opening of the Alpine Tethys, or (ii) multiple, distinct rifting events, predating the onset of the Alpine cycle. Our study focuses on the European western Southern Alps (Varese area, N. Italy), where we document the tectonic events from the early Permian to the Middle Triassic. Through a combined tectono-stratigraphic and thermochronological analysis, we identify an initial early Permian rifting stage linked to magmatic activity, followed by early–middle Permian transcurrent tectonics. This phase is truncated by a middle Permian regional-scale erosional event that marks the cessation of this tectonic phase. Subsequently, during the Middle Triassic, a second phase initiated, which we interpret as the onset of the Alpine Tethys opening. This phase likely corresponds to an early stretching stage that predates the well-documented Late Triassic crustal-thinning phase. Based on our findings, we propose that the Middle Triassic stretching phase represents the first stage of the Alpine Tethys rifting, thereby challenging the hypothesis of a continuous Permo-Triassic long-lasting extension.